Negative refraction in hyperbolic metamaterials - Leow, Ee Kiat (Nanyang Technological University, 2020)
This project investigates the negative refraction in a way that is not observed in nature. All stimulations are done on the Multiphysics software COMSOL to replicate the materials and light beam needed to theorize the findings of negative refractions. The project consists of two main sections, firstly, we would have to find the wavelength that negative refraction would occur by engineering the permittivity and permeability of the materials and then by using this wavelength and its desired permittivity and permeability to create a metamaterial in COMSOL to observe two phenomenon, mainly type II metamaterial as well as a multilayered metamaterial for real world application. This project also further investigates the semiconductor materials in replacement of the metal for the homogeneous medium.